(untitled) (Bangladesh Journal of Endosurgery, 2013)
Purpose: Inguinal hernia is one of the commonest conditions in paediatric surgical practice that requires surgical repair. Open repair is a conventional procedure. With the advance of minimally invasive surgery, laparoscopic repair of childhood inguinal hernia has been attempted. Now many centres practice it routinely. From different studies, reported advantages are excellent visual exposure, minimal dissection, and thus fewer trauma to the inguinal canal and its content, detection, and repair of contralateral hernia (if present) in same setting, less post-operative pain, early recovery, and better cosmesis. To date, despite increased interest in laparoscopic repair, there is no published study focusing on paediatric inguinal hernia in Bangladesh. So the present study is designed to assess the above mentioned clinical benefits of this method and to compare the laparoscopic repair and open repair of paediatric inguinal hernia. Materials and Methods: This prospective comparative interventional study was carried out in the Department of Paediatric Surgery, DMCH, Dhaka, during the period of May 2009 to June 2012. Total 60 patients were included in this study. Among them 30 patients in Group-L were repaired by laparoscopic procedure and another 30 patients in Group-O were repaired by open procedure. Both groups were followed-up for 3 months. The early post-operative complications were almost same and there was no recurrence in any groups. Results: It was found that laparoscopic repair is superior to open repair with regards to early pain relief and cosmesis. Moreover, on laparoscopy, detection of contralateral hernia or contralateral patent processus vaginalis and repair is possible in the same setting. Conclusions: Laparoscopic repair is superior with regard to early pain relief and cosmesis, but needs to be evaluated on wider group of patients and long period of follow-up. DOI: http://dx.doi.org/10.11593/bje.2013.0102.0014 Bangladesh Journal of Endosurgery Vol.1(2) May 2013: 29-34